Financial development and macroeconomic performance : a cointegration approach - Ferreira, Cândida (2020)
The paper tests the existence of long-term relations, measured through cointegration, between all the IMF financial development indices and some macroeconomic performance indicators applying panel cointegration tests in a panel with 46 countries, and in a panel including only the sub-sample of the 28 EU countries over the interval 1990-2017. Overall, there are no significant differences between the results obtained for whole sample and the panel including only the EU countries. The results obtained clearly point to the existence of cointegration between the financial development indices and the real Gross Domestic Product, as well as with the inflation, the unemployment rate, and very particularly, with the current account, and with the net international investment position. The results also show there are no significant differences between the results obtained for the financial institutions and for the financial markets. Moreover, the results related to the specific aspects addressed by the IMF indices very well demonstrate that much more important than the simple access to or the depth of the financial institutions and markets is the efficiency of these institutions and markets.